Essays on the role on informality, corruption and social networks in Brazil - Magalhães, Marcos Renan Vasconcelos (2023)
This thesis is composed of three essays on informality, corruption and social networks and their respective dynamics with macroeconomic aggregates based on microfoundations. In the chapter, we study an equilibrium two-sector occupational choice model - agents can be (formal or informal) entrepreneurs or workers. An informal entrepreneur faces taxation determined by the combination of her capital choice and society’s tolerance of informality. Our model is consistent with many empirical ndings regarding the informal sector in Brazil, a developing economy with a large informal sector. With a calibrated version of our model, we show that as society’s tolerance of informality decreases, the informal sector employs less capital and labor, and informality decreases. We conduct several counterfactual exercises. Informality is substantially lower in economies that are less tolerant of informal activities, formal entrepreneurs have more access to nancial markets, and taxation of output and labor is lower. We extend the model to consider stochastic taxation of informal activities - a higher (average) informal output taxation and its variability reduce informality. In the second chapter, we present a model in which the embezzlement of tax revenues by public ofcials imposes distortionary effects on economic performance through its dentrimental effect on the private sector. The contribution of this article, in addition to the empirical evidence presented, is the study of a tractable economy in which it is possible to evaluate the responses of economic aggregates, via steady state analyzes and dynamic responses to variations and corruption shocks. Our model is consistent with many empirical findings about the Brazilian economy, such as the level of GDP lost to corruption and the number of corrupt bureaucrats. With a calibrated version of our model for the Brazilian economy, we study the quantitative implications of changes in the level of corruption on economic performance by comparing steady state and transition paths of the variables. Overall, our results show that economies with higher corruption control tend to present a better economic performance, with a higher level of output, capital stock, consumption, investment, tax collection and wages. The last article improves the model presented in the second chapter, examining the relationship between social networks and the spread of corruption. We argue that social networks in labor market can facilitate corruption propagation by providing corrupt oficials with opportunities to meet and collude with each other. We develop a model of social networks and corruption propagation in witch workers are endowed with peers exogenously and engage in network search to affect their labor market outcomes. We assume that power-law distributions govern the structure of social networks. We show that a shock on corrupt vacancies initially boosts the rate at which corrupt opportunities appear. Corruption-induced distortions have an adverse effect on the economy’s productivity, leading to reduced demand for capital. These consequences are particularly noticeable in economies where the average number of peers is higher. Concerning the technology shock, there is a positive effect on all components of aggregate demand. Nonetheless, the infuence on the arrival rate of corrupt opportunities varies depending on how we represent the effect on the economy’s output. In one approach, the effect aligns with the notion of hindrance (akin to the "sand-in-the- eels"hypothesis), while in another, it resembles a facilitation (akin to the "grease-in-the-wheels"hypothesis). Our ndings suggest that social networks can play a role in facilitating corruption propagation. Policies should be aimed at weakening labor market networks and increasing the transparency of government procurement and contracting processes.